PROFILE OF PGMI (PRIMARY MADRASAH TEACHER EDUCATION) STUDENTS IN THE LEVEL OF HASS GEOMETRY IN DECISION MAKING - Margaretha, Puspita Maya; Wijaksono, Agung (International Journal of Multidisciplinary Reseach, 2025)
This study describes the profiles of students with low, medium, and high levels of geometric ability. These profiles serve as benchmarks to analyze student typologies in terms of economic behavior, particularly in classifying them as either thrifty savers or highly consumptive individuals. The study employs a qualitative descriptive method, involving a sample of 9 students selected from a population of 500. Referring to previous research on geometric ability based on Hass’s Theory, students are categorized according to their capabilities in visualization, conceptualization, pattern recognition, and problem-solving. The findings show that 100% of students with high geometric ability opted for saving behavior. Meanwhile, 70% of students with medium geometric ability chose to save, while the remaining 30% exhibited fully consumptive behavior. In contrast, none of the students with low geometric ability chose to save; all of them demonstrated high consumerism. In this study, saving behavior is referred to as being a “thrifty client.” It is expected that future research will provide interventions for students with low geometric ability using Hass’s geometric theory, aiming to shift their behavior towards saving and thus becoming thrifty clients. In the long term, such efforts are anticipated to help reduce consumptive behavior both at the local and global levels.